Slippery hill-climbing technique for ciphertext-only cryptanalysis of periodic polyalphabetic substitution ciphers. Issue 3 (3rd May 2020) - Kaeding, Thomas
Abstract: We present a stochastic method for breaking general periodic polyalphabetic substitution ciphers using only the ciphertext and without using any additional constraints that might come from the cipher's structure. The method employs a hill-climbing algorithm for individual key alphabets, with occasional slipping down the hill. We implement the method with a computer and achieve reliable results for a sufficiently long ciphertext (150 characters per key alphabet). Because no constraints among the key alphabets are used, this method applies to any periodic polyalphabetic substitution cipher.